2002
DOI: 10.1007/s00330-002-1376-4
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study for the evaluation of a dedicated biopsy device for MR-guided vacuum biopsy of the breast

Abstract: The purpose of this multicenter study was to determine the accuracy and clinical value of a dedicated breast biopsy system which allows for MR-guided vacuum biopsy (VB) of contrast-enhancing lesions. In five European centers, MR-guided 11-gauge VB was performed on 341 lesions. In 7 cases VB was unsuccessful. This was immediately realized on postinterventional images or direct follow-up combined with histopathology-imaging correlation; thus, a false-negative diagnosis was avoided. Histology of 334 successful bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
3
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 15 publications
3
57
3
7
Order By: Relevance
“…The number of underestimates identified at follow-up surgery or imaging was not reported (Table 5). Perlet et al (21,22) reported interim results of a prospective, multicenter study of MR-guided breast biopsy in 2002, and published the final results in 2006. As with the study reported by Viehweg et al, an adaptation of the original stereotactic Mammotome was used to perform the MRI-guided biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…The number of underestimates identified at follow-up surgery or imaging was not reported (Table 5). Perlet et al (21,22) reported interim results of a prospective, multicenter study of MR-guided breast biopsy in 2002, and published the final results in 2006. As with the study reported by Viehweg et al, an adaptation of the original stereotactic Mammotome was used to perform the MRI-guided biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Nur in der Magnetresonanztomographie sichtbare Lä-sionen müssen auch unter magnetresonanztomographischer Kontrolle minimal-invasiv biopsiert werden [3,18,19]. Da bei der magnetresonanztomographisch gesteuerten Intervention, wie bei der mammographischen Stereotaxie, keine direkte Kontrolle des Biopsievorganges mög-lich ist, ist auch in diesen Fällen die Anwendung der vakuumunterstützten Verfahren zu empfehlen (Abb.…”
Section: Wahl Der Lokalisationsmethode Bei Unklaren Oder Suspekten Beunclassified
“…Da bei der magnetresonanztomographisch gesteuerten Intervention, wie bei der mammographischen Stereotaxie, keine direkte Kontrolle des Biopsievorganges mög-lich ist, ist auch in diesen Fällen die Anwendung der vakuumunterstützten Verfahren zu empfehlen (Abb. 4) [3,18,19].…”
Section: Wahl Der Lokalisationsmethode Bei Unklaren Oder Suspekten Beunclassified
See 1 more Smart Citation
“…A computer-assisted diagnostic system that improves accuracy and speed of the procedure is also commercially available. About 8-13% of MRIguided biopsy target lesions are not visible at the time of biopsy (21)(22)(23). If the target is not visible on the first postcontrast image, it is sometimes identified on a delayed image.…”
Section: Equipmentmentioning
confidence: 99%